Time-dependent Expression of Nrf2 Protein and its Effects on Wound Repair in Skeletal Muscle - ZHANG Xiao-Hong, LIU Ji, LI Na-1，et al (Fayixue Zazhi, 2018)
Objective To detect the expression of nuclear factor erythroid 2-related factor 2 （Nrf2） to explore its change rule and effects in the repair process of skeletal muscle. Methods An injury model of skeletal muscle was established by injection of cardiotoxin into the gastrocnemius muscle of SD male rats. The muscle samples were taken from control group and injury group at each time point （1 h, 4 h, 8 h, 12 h, 16 h, 1 d, 3 d, 5 d, 7 d, 9 d, 13 d, 17 d, 21 d）. The morphological changes of skeletal muscle in repair process were observed by H&E staining, and the content of reactive oxygen species （ROS） was detected. The expression level of Nrf2 protein was investigated by Western blotting and immunohistochemistry staining. Results After the skeletal muscle injury, the injury region was infiltrated with inflammatory cells which constituted mainly by lymphocyte neutrophils and mononuclear cells. There were large amounts of immature muscle cells appeared at the 5th day and the muscle repair was completed at the 21th day. Comparing with control group, the ROS content decreased in injury group at the 12th hour （P<0.05）, while Nrf2 expression increased at the 16th hour （P<0.05）. Moreover, the positive rate of Nrf2 increased after injury, and peaked at 16 h-1 d, then decreased gradually and returned to the level of control group （P<0.05）. Conclusion The Nrf2 protein involves in the regulation of the repair of skeletal muscle injury. The positive rate of Nrf2 shows a time-dependent expression, which can be used to estimate the wound age of skeletal muscle.